ARTIFICIAL NEURAL NETWORK AS A TOOL FOR JUDICIAL DECISION-MAKING IN THE ANGLO-SAXON LAW SYSTEM - Алешин, Сергей; Гайтан, Елена (Modern engineering and innovative technologies, 2022)
Case law is a legal system in which judicial precedent is recognized as the main source of law; it is a decision made in any case that is binding on all courts of equal and lower instance when they consider similar cases. In the precedent system of law ju